(untitled) (Journal of Enam Medical College, 2024)
Background: Cranioplasty is a straightforward procedure; it may result in a significant number of complications. These include infections, seizures, intracranial hematomas, and others. Objective: To evaluate the outcome following cranioplasty with titanium mesh-plate and screw. Materials and Methods: This retrospective study included patients who underwent decompressive craniectomy due to traumatic brain injury with raised intracranial pressure, acute subdural hematoma, compound comminuted skull fracture and intracranial hemorrhage, between January 2019 to December 2020 at Enam Medical College Hospital, Savar, Dhaka. Data were collected in pre-designed data collection sheet and were analyzed using computer-based programme statistical package for social science (SPSS) windows version 25.0. Results: This study showed maximum patients (34.2%) were between 21-30 years age. Majority (89.5%) were male and only 5.9% were female. Overall rate of complications was 10.5%. Among them new onset seizure was four, indrawing of skin through bone gap was four, hemorrhage was two, infection was one, hydrocephalus was one, and exposed implant also one. Conclusion: We have found the outcome of cranioplasty was better with titanium mesh plate and screw than conventional fixation of bone with polyglactin, polypropylene suture and titanium miniplate and screw. With polypropylene and polyglactin there is more chance of inward displacement of bone fragment and with miniplate and screw there is still chance of indrawing of bone fragment through the bone gap. J Enam Med Col 2022; 12(2): 90−94